187 Gas production dynamics of salts of volatile organic acids incubated with Brachiaria brizantha cv. Marandu. (29th July 2019) - Batista, Luiz Fernando Dias; Cagle, Caitlyn; Norris, Aaron; Ferro, Mariane; Crossland, Whitney; Tedeschi, Luis Orlindo
Abstract: An in vitro gas production technique was used to obtain the fermentation dynamics of seven encapsulation methods (TRT:S1, S2, S3, S4, S5, S6, S7) and two levels of inclusion (LI: L3 = 3% of DM and L6 = 6% of DM) of salts of volatile organic acids (VOA). The encapsulation methods had different levels and material sources (NutriCattle, Brazil): dioxides and maltodextrins (S1, S2, S4, S6, and S7) and celluloses (S3, S4, S5, and S6). A total of 200 mg of air-dried Brachiaria brizantha hay plus salts were incubated for 48 h with rumen fluid collected from two ruminal-cannulated grazing steers. Six incubations were obtained with (n = 3) or without (n = 3) the additions of casein and cysteine (CC). The exponential nonlinear function with lag was fitted to the accumulated gas data without adjusting for blank, and the parameters were analyzed assuming runs (n = 6) as random effects and either TRT, LI, and CC or TRT and LI as fixed effects by CC. Methane (CH4 ) measurements were obtained via gas chromatography. The inclusion of CC increased gas production (mL, P = 0.08) and the rate of fermentation (1/h, P = 0.002). When CC was included, S3 (40.6) and S1 (40.1mL) produced more gas (P4 intensity was greater (P = 0.053) for S3 (94.9), S1 (92.6), S4 (91.7), and S2 (90) than S6 (81.7), S5 (81.5), and S7 (81.3 mg/g fermentable organic matter). When CC was not included, L3 (36.1) produced more gas (PP4 intensity was greater (P = 0.001) for L3 (77.5) than L6 (70.1 mg/g). These analyses suggested that encapsulation methods and dietary true protein content impact fermentation dynamics of B. brizantha and the intensity of CH4 .